Pengaruh Kualitas Produk, Kepuasan Pelanggan Dan Kepercayaan Pelanggan Terhadap Loyalitas Pelanggan Sun Care Wardah Di Kota Batam - Nur Oktaviani; Sukati, Inda (SCIENTIA JOURNAL, 2025)
This study aims to analyze the effect of product quality, customer satisfaction, and customer trust on customer loyalty of Sun Care Wardah in Batam City. The research approach used is quantitative with a descriptive design. Respondents in this study were consumers of Sun Care Wardah in Batam City in 2024 with an unknown number. The sample determination was carried out using the Jacob Cohen formula which resulted in 204 respondents and the purposive sampling method was applied as a sampling technique based on certain criteria. The analysis techniques applied include data quality testing, classical assumption testing, influence analysis, and hypothesis testing. The results showed that product quality contributed 21.5% to customer loyalty, customer satisfaction had an influence of 33.0%, and customer trust contributed 18.3%. The coefficient of determination (R²) shows that product quality, customer satisfaction, and customer trust together influence customer loyalty by 68.3%, while the rest is influenced by other factors outside the scope of the study. Statistical tests using the t-test and F-test confirmed that product quality, customer satisfaction, and customer trust have a positive and significant effect on customer loyalty of Sun Care Wardah in Batam City.